MOTIF CERAI GUGAT PADA PEREMPUAN DI DESA SUKOREJO KECAMATAN BOJONEGORO KABUPATEN BOJONEGORO - Vera Chontesa; Jatiningsih, Oksiana (Kajian Moral dan Kewarganegaraan, 2025)
This study aims to explore the motives behind divorce lawsuits filed by women in Sukorejo Village, Bojonegoro Sub-district, Bojonegoro Regency, and to determine whether gender understanding influences such actions. The research uses a qualitative approach with Alfred Schutz's phenomenological theory, which emphasizes understanding the subjective meaning of individual social actions. Data were collected through in-depth interviews with five female informants who had filed for divorce. The findings indicate that there are several motives behind women's decisions to divorce their husbands. The "because motives" include infidelity, economic hardship, ongoing conflicts, and domestic violence. Meanwhile, the "in-order-to motives" include escaping a partner’s betrayal, seeking peace of mind, protection, and a sense of security. This study also found that, based on the interview results, the majority of informants filed for divorce with a limited understanding of gender concepts.